2019
DOI: 10.1016/j.ijid.2019.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium difficile infections among Kenyan children with diarrhea

Abstract: Clostridium difficile infections in Africa C. difficile pathogenesis C. difficile epidemiology CDI in young children CDI in infants C. difficile co-infection A B S T R A C TBackground: Diarrhea causes significant morbidity and mortality among children worldwide. Regions most affected by diarrhea include Sub-Saharan Africa and Southeast Asia, where antibiotics are in common use and can make children more vulnerable to Clostridium difficile and pathogens that are not affected by these drugs. Indeed, C. difficile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…Postbiotics may also be a new alternative to prevent or treat Clostridioides difficile (formerly known as Clostridium difficile ) infections (CDI). Although considered extremely rare in neonates and infants, further studies report the occurrence of diarrhea in this specific population [ 91 , 92 ]. Routine testing for CDI in infants is currently not recommended due to the high asymptomatic colonization in this group and should be performed only when other causes of diarrhea, such as rotavirus, have been excluded [ 93 , 94 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postbiotics may also be a new alternative to prevent or treat Clostridioides difficile (formerly known as Clostridium difficile ) infections (CDI). Although considered extremely rare in neonates and infants, further studies report the occurrence of diarrhea in this specific population [ 91 , 92 ]. Routine testing for CDI in infants is currently not recommended due to the high asymptomatic colonization in this group and should be performed only when other causes of diarrhea, such as rotavirus, have been excluded [ 93 , 94 ].…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…Routine testing for CDI in infants is currently not recommended due to the high asymptomatic colonization in this group and should be performed only when other causes of diarrhea, such as rotavirus, have been excluded [ 93 , 94 ]. However, toxigenic C. difficile has been identified alone or in co-infection with rotavirus, suggesting that it could be a contributing factor to diarrhea in infants [ 92 , 95 ]. New evidence shows that CFS from various lactic acid bacteria (LAB) cocultured with multi-resistant C. difficile can reduce the cytotoxic effects of clostridial toxins on different cell lines compared to pure C. difficile CFS.…”
Section: Potential Mechanisms Of Actionmentioning
confidence: 99%
“…There are scarcity of data published and information sharing platforms on CDI epidemiology in sub-Sahara Africa [6,7]. Little is documented on the risk factors and prevalence of C. difficile in hospitals and community health care settings in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also found lower Cryptosporidium spp. prevalence in Kenyan children with diarrhoea of 5.1% [26] or 11.0% [27], respectively. In contrast, the prevalence found in the present study was much lower than that previously reported (34.1%) in HIV infected individuals [9].…”
Section: Discussionmentioning
confidence: 99%